Assessment of Human Health Risk Caused by Heavy Metals in Kiln Dust from Coal-Fired Clay Brick Factories in Türkiye - Turhan, Şeref; Altuner, Ergin Murat; Bakır, Temel K.; Duran, Celalettin; Hançerlioğulları, Aybaba; Kurnaz, Aslı (Springer Science and Business Media LLC, 2024)
Abstract Heavy metal (HM) pollution from natural processes and different anthropogenic activities pose significant human and environmental health risks because of their stability, non-degradable properties, and high toxicity. HM released into the air in the form of dust can enter the human body via ingestion, inhalation, and dermal contact. Keeping in mind the significance of estimating the risk from HM in different environments, the carcinogenic and non-carcinogenic health risks to workers caused by HM in kiln dust (KD) samples collected from coal-fired clay brick factories in the Western Black Sea Region of Türkiye were assessed for the first time in this study. The concentrations of major and minor oxides and HMs in the collected KD samples were analyzed using energy-dispersive X-ray fluorescence spectrometry. The average concentrations of Fe, Mn, Cr, Ni, V, Zn, Cu, As, Co and Pb analyzed in thirty-three KD samples were determined as 65444, 768, 251, 249, 248, 122, 60, 52, 42 and 16 mg/kg dw, respectively. The average levels of Ni, As, Cr, Co and Cu exceed the maximum contaminant levels recommended in the Turkish Regulation on Control of Soil Pollution. Carcinogenic and non-carcinogenic human health risk assessments for workers via three exposure pathways were carried out, estimating the hazard index (HI) and total carcinogenic risk (TCR) index, respectively. The HI values (< 1) revealed no possible non-carcinogenic health risk due to exposure to all HMs in the studied KD samples. The average TCR value revealed that the potential cancer risks for Ni, As, Cr, and Pb were slightly above the safe limit and required monitoring and further investigation for these HMs.
Keywords: 13. Climate action; 6. Clean water; 3. Good health